Christian Spiritual Music Therapy Against Patient Anxiety In the Emergency Room - Samy Rensya; Suhartini Ismail; Samuel Saiselar; Acmad Zulfa Juniarto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to obtain a comprehensive picture of the effect of spiritual music therapy on reducing anxiety in patients in the emergency room (IGD). The method used in this research is a scoping review. Article searches used databases from Sciencedirect, PubMed, Sciencedirect, and Scopus. The keywords used are (“Patient Anxiety,” “Spiritual,” AND “Music Therapy). The results of the study showed that there was an effect of listening to Christian spiritual music on patient anxiety in the inpatient room. In conclusion, Christian spiritual music has proven to be significant in reducing patient anxiety, both mild anxiety and moderate anxiety, while in the ER. Keywords: Anxiety, Christian Spiritual Music